THE REGULATION OF ADVICE WITHIN THE FINANCIAL SERVICES SECTOR* - Henk Kloppers (Obiter, 2022)
The Financial Services Sector has undergone quite significant legislative changes in the last number of years. These changes were mainly facilitated through the Financial Advisory and Intermediary Services Act (37 of 2002, hereinafter “the FAIS Act” or “FAIS”) together with the Policyholder Protection Rules (Long-Term Insurance) 2001 (GN R165 in GG 22085 of 2001-02-23) and the Policyholder Protection Rules (Short-Term Insurance) 2001 (GN 164 in GG 22084 of 2001-02-23). These rules were promulgated in terms of section 62 of the Long-Term Insurance Act (52 of 1998). However, the content of these rules was to a large extent duplicated in the General Code of Conduct for Authorised Financial Services Providers and Representatives (BN 80 of 2003, hereinafter “the Code of Conduct”). One of the main purposes of this legislation is the regulation of advice in order to enable clients to make informed decisions with regard to financial products and to ensure that intermediaries (commonly referred to as “brokers”) and insurers conduct business honestly and fairly, and with due care and diligence. The Act is ultimately aimed at the protection of consumers. It can be regarded as market conduct legislation as it provides for the regulation of the conduct of specifically providers of financial services and their representatives. Although financial advisors are still playing the same game, the FAIS Act has effectively changed the rules of the game. Financial advisors are consequently faced with the following decision: Accept the new rule changes and adapt your business to be consistent with legislation, or decide that the rule changes are too drastic and stop playing altogether. The FAIS Act, however, also created the need for a referee to ensure that all the players play according to the new rules. In this regard, Part IV of the Act made provision for the establishment of the Ombud for Financial Services Providers. The Office of the Ombud became operational in 2005 and has since received numerous complaints regarding the furnishing of advice and has made several determinations. (Determinations of the Ombud can be accessed www.faisombud.co.za.) This note will examine the relevant sections in the legislation dealing with the regulation of advice. The position of the FAIS Ombud will be considered and recent determinations made by the Ombud on the subject of the furnishing of advice will be discussed.